Screening for vitamin B-12 and folate deficiency in older persons - SCOTT, JOHN MARTIN (American Society for Clinical Nutrition, 2003)
Background: Vitamin B-12 deficiency is usually accompanied by elevated concentrations of serum total homocysteine (tHcy) and methylmalonic acid (MMA). Folate deficiency also results in elevated tHcy. Measurement of these metabolites can be used to screen for functional vitamin B-12 or folate deficiency. Objective: We assessed the prevalence of vitamin B-12 and folate deficiency in a population-based study (n = 1562) of older persons living in Oxford City, United Kingdom. Design: We postulated that, as vitamin B-12 or folate concentrations declined from adequate to impaired levels, tHcy (or MMA) concentrations would increase. Individuals were classified as being at high risk of vitamin B-12 deficiency if they had low vitamin B-12 (< 150 pmol/L) or borderline vitamin B-12 (150?200 pmol/L) accompanied by elevated MMA (> 0.35 ?mol/L) or tHcy (> 15.0 ?mol/L). Individuals were classified as being at high risk of folate deficiency if they had low folate (< 5 nmol/L) or borderline folate (5?7 nmol/L) accompanied by elevated tHcy (> 15 ?mol/L). Results: Cutoffs of 15.0 ?mol/L for tHcy and 0.35 ?mol/L for MMA identified persons with normal or elevated concentrations. Among persons aged 65?74 and 75 y, respectively, 10% and 20% were at high risk of vitamin B-12 deficiency. About 10% and 20%, respectively, were also at high risk of folate deficiency. About 10% of persons with vitamin B-12 deficiency also had folate deficiency. Conclusion: Use of tHcy or MMA among older persons with borderline vitamin concentrations may identify those at high risk of vitamin B-12 deficiency who should be considered for treatment.
PUBLISHED
Keywords: Screening ? folate ? vitamin B-12 ? homocysteine ? methylmalonic acid ? elderly